Palladium‐Catalyzed α‐Arylation Reactions in Total Synthesis. Issue 1 (19th November 2014) - Sivanandan, Sudheesh T.; Shaji, Ashna; Ibnusaud, Ibrahim; Seechurn, Carin C. C. Johansson; Colacot, Thomas J.
Abstract: The development of palladium‐catalyzed α‐arylation of carbonyl compounds has emerged as a new avenue in the design of new routes for the synthesis of natural products and active pharmaceutical ingredients (APIs). In many cases, syntheses based on α‐arylation strategies provide elegant routes in terms of increasing the overall yields, improving the synthesis scope, and decreasing the number of steps. This microreview aims to highlight the importance of palladium‐catalyzed α‐arylation methodologies, covering a range of notable reported examples of the total syntheses of structurally important compounds, thereby highlighting the importance of this powerful methodology for key steps in organic synthesis. Abstract : Metal‐catalyzed α‐arylation of carbonyl compounds has become a powerful tool for organic chemists to construct carbon‐carbon bonds through C–H functionalization based on enolization. This microreview highlights recent applications of α‐arylation in total syntheses both of natural products and of active pharmaceutical ingredients (APIs).